Prevalência de síndrome metabólica, associação com fatores de risco e complicações cardiovasculares na população adulta de São José do Rio Preto - Moreira, Gisela Cipullo (2012)
Introduction: Metabolic Syndrome (MS) is a set of cardiovascular risk factors and type 2 diabetes, responsible for increased cardiovascular mortality in 2.5-fold and in 5-fold in risk of developing diabetes. Objectives: This study aims to evaluate in age over 18 years, the prevalence of MS associated to age, gender, socioeconomic status, educational levels, body mass index, HOMA index, physical activity, to compare the prevalence of high levels of triglycerides (TG), elevated blood pressure, altered plasma glucose levels, low HDL cholesterol and measure the waist change among individuals with MS and also according to gender; evaluate the number of risk factors in subjects with metabolic syndrome and prevalence of cardiovascular and renal complications in individuals with and without the syndrome, aged over 40 years. Casuistics and Methods: In this randomized cross-transversal study, a sample of 1369 individuals aged over 18 years, 667 males (48.7%) and 702 females (51.3% ) to evaluate the prevalence of metabolic syndrome and associated factors in the adult population. Results: In relation of MS prevalence level, it was observed that 22.7% (95% CI: 19.4% to 26.0%) of the population has the syndrome, that increases with age, increased body mass index and sedentary lifestyle, with no significant differences between genders until age ≥ 70 years, when it begins to predominate in women. No significant difference between social classes, but there was a higher prevalence of MS in lower educational levels. It was observed that individuals with MS have higher prevalence of HOMA positive. The risk factors most prevalent in MS were elevated blood pressure, low HDL cholesterol and increased waist circumference. The prevalence of elevated blood pressure, low HDL cholesterol and plasma glucose levels have not changed significant difference between genders. Among men, the prevalence is similar among the risk factors, being more frequent in women the increased waist circumference. People with MS will have from 40 years of higher prevalence in the occurrence of complications. Conclusion: The prevalence of MS found is similar to developed countries, being influenced by age, body mass index, educational levels, physical activity, leading from the 4th decade of life, the higher prevalence of complications such as stroke, coronary arterial disease, angina, myocardial revascularization, heart failure and / or renal impairment.